Alkaline coagulation for separation of outdoor anaerobically cultured microalgae using natural-based coagulant - James, Abraham O. [UNESP]; Bankole, Abayomi O. [UNESP]; Moruzzi, Rodrigo [UNESP]; Silva, Gustavo H.R. [UNESP] (Elsevier, 2025)
Although, native microalgae (MA) grows in alkaline environments, there is a lack of information from previous studies on the separation of microalgae culture under alkaline coagulation-flocculation-sedimentation (CFS) conditions. This study evaluated the separation efficiency of tannin (TA), Moringa oleifera seed extract (MOSE) natural coagulants in comparison with Aluminum sulfate (AS) for harvesting MA grown in anaerobically digested sanitary wastewater in a pilot flat panel photobioreactor in outdoor environment. The aim was to establish a pathway for recovery of microalgae biomass and supernatant without pH control and save cost for pH adjustment chemicals, in alignment with the circular economy concepts. Total suspended solids (TSS), turbidity and MA concentration (optical density – OD) were monitored throughout the tests. Optimum dosages of TA (1100 mg l−1), MOSE (3000 mg l−1) and AS (320 mg l−1) determined from jar tests were evaluated after MA cultivation, with natural pH of 10.4 under CFS condition (Coagulation: velocity gradient (Gf) of 200 s−1 for 2 min, flocculation: Gf of 10 s−1 for 15 min and sedimentation: 10 min observation time). TA and AS presented similar high removal efficiencies for turbidity (≥ 95 %), OD (≥ 87 %) and TSS (≥ 62 %). However, TA recorded a good pH (7.6) for the supernatant compared to an unsatisfactorily low 5.2 for AS. TA presented the potential of harvesting MA biomass without prior pH control and without adversely impacting the medium's pH. This shows that biomass has a potential usage as a biofertiliser and as well the resultant supernatant is reusable for non-potable purposes.
Keywords: Alkaline coagulation; Biofertilizer; Circular economy; Natural coagulants; Separation efficiency